Analyzing Speech Acts in School Communication: A Study of Abbott Elementary Series - Sanjaya, Paschalis Kurniawan; Lumintang, Sheline Feranda; Ena, F.X. Ouda Teda (Universitas Negeri Makassar, 2025)
Abstract. To understand how individuals convey meaning or information, manage relationships with others, and navigate power dynamics in communication, one needs to know the meaning and types of speech acts especially. This study aims to analyze school communication in the Abbott Elementary series through the lens of speech act theory, focusing on how different types of illocutionary acts are used to shape classroom interactions. This research provides a novel contribution to the linguistic field by analyzing speech acts specifically in the educational setting. This study uses a qualitative approach to explore communication dynamics by using discourse analysis to identify and categorize the illocutionary acts present in the three episodes in the first series to answer the first problem. Then, the data obtained will also be calculated and analyzed to answer the second research question, namely the type of speech acts that appear most often. As a result, this study found that the series includes all five types of speech acts in its communication, and the representative type has the highest intensity of occurrence in the three episodes of the first series that was studied. This finding can provide valuable insight into the role of language, especially in the educational environment Keywords: Abbott Elementary, School Communication, Speech Act